Efficacy of dynamic humeral centering according to Neer test results: a stratified analysis of a randomized-controlled trial. Issue 1 (March 2015) - Beaudreuil, Johann; Ostertag, Agnès; Lasbleiz, Sandra; Vicaut, Eric; Yelnik, Alain; Bardin, Thomas; Orcel, Philippe
Abstract : The aim of this study was to assess the efficacy of dynamic humeral centering (DHC) according to Neer test results. The study was a stratified analysis of a previously reported randomized trial. The patients included had shoulder pain with impingement syndrome. Interventions were DHC or nonspecific mobilization for control. The primary outcome was the Constant score including subscores for pain, activity, mobility, and strength at 3 months. All patients improved at follow-up, with better results after DHC. There was no interaction between Neer test results, treatments, and time. However, a trend toward higher effect sizes was observed after DHC in patients with a positive Neer test in comparison with negative patients. Patients with a positive Neer test showed improvement after DHC for rotator cuff disease compared with nonspecific mobilization.